The relationship between intimate partner violence and child malnutrition: a retrospective study in 29 sub-Saharan African countries - Lin, Kunhong; Zhou, Pengxiang; Liu, Mengyuan; Chen, Botian; Zhou, Zibei; Zhang, Yijia; Zhou, Ying; Jiang, Yanan; Bao, Shuyun; Chen, Dijia; Zhu, Yu; Xing, Yan (Frontiers in Public Health, 2024)
Intimate partner violence (IPV) and child malnutrition are global public health issues.Assessing the association between IPV and child anthropometric failures (stunting, underweight, wasting) in 29 Sub-Saharan Africa (SSA) countries can provide significant global health solutions. Some studies have found an association between IPV against women and child malnutrition, but the conclusions are inconsistent. The physical and psychological conditions, living environment, and rights of the mother may be involved.We collected and analyzed 29 SSA countries ' Demographic and Health Surveys data (2010-2021). The main exposure variables were various types of IPV, classified as physical, sexual and emotional violence. The outcome was the child's development index, which can be roughly divided into stunting, wasting, and underweight. An adjusted binary logistic regression model was used to test the relationship between IPV and children's nutritional status. 186,138 children under 5 years old were included in the analysis; 50,113 (27.1%) of the children were stunted, 11,329 (6.1%) were wasted, and 39,459 (21.3%) were underweight in all regions. The child's gender, age, duration of breastfeeding, complementary feeding, and use of vitamin A in the past six months were associated with their nutritional status (P <0.001). Sexual violence was the strongest factor associated with stunting, which remained statistically significant after controlling all variables (AOR = 1.11, 95% CI:1.02, 1.21, P=0.012). We also found a small negative association between wasting and IPV. For underweight, there was no associations with IPV after controlling for all variables (P > 0.05). IPV is positively associated with child stunting in SSA countries.Sexual violence showed a strong positive correlation with stunting. Wasting was unexpectedly negatively associated with IPV. There was no clear correlation between underweight and violence.